The Effectiveness of a Digital Art-Based Social-Emotional Learning (SEL) Program on Reducing Aggression in Elementary School Students: An Intervention Study - Athar Rafati; Seyedeh Nafiseh Mohseni Mansour; Hanieh Abbasi; Mehrnoosh Ranjbar; Fakhri Sadat Hosseini (AI and Tech in Behavioral and Social Sciences, 2026)
Aggression during the early school years interferes with peer relationships, classroom adjustment, and academic functioning. School-based social-emotional learning (SEL) programs can reduce behavioral problems, yet children may benefit most from formats that are developmentally engaging and expressive. This study examined whether a digital art-based SEL program could reduce aggression in second-grade students.A quasi-experimental pretest-posttest design with a control group was used. Fifty-two second-grade students from public elementary schools in Mazandaran Province, Iran, were selected through cluster sampling and assigned to an experimental group (n = 28) or a control group (n = 24). Aggression was assessed at baseline and post-intervention using the Persian version of the Buss-Perry Aggression Questionnaire. The experimental group participated in an eight-week intervention comprising 16 sessions (two 60-minute sessions per week) integrating CASEL-based SEL competencies with digital art activities, whereas the control group continued routine instruction. Descriptive statistics and mixed-design ANOVA were used for analysis. The groups were comparable at baseline on demographic characteristics and aggression scores. From pretest to posttest, the experimental group showed marked reductions in total aggression (47.85 ± 5.20 to 31.80 ± 4.50), physical aggression (12.45 ± 2.10 to 8.30 ± 1.85), verbal aggression (11.80 ± 2.40 to 7.50 ± 1.90), anger (13.10 ± 2.60 to 9.20 ± 2.10), and hostility (10.50 ± 2.30 to 6.80 ± 1.70), whereas changes in the control group were small. Mixed ANOVA showed a significant group × time interaction for total aggression, F(1, 50) = 26.07, p = .001, η² = .34, as well as for physical aggression, F(1, 50) = 22.15, p = .001, η² = .31; verbal aggression, F(1, 50) = 18.92, p = .001, η² = .27; anger, F(1, 50) = 24.56, p = .001, η² = .33; and hostility, F(1, 50) = 19.45, p = .001, η² = .28. A digital art-based SEL program appears to be an effective and engaging school-based approach for reducing aggression in elementary school students. Larger multi-site studies with follow-up assessments are recommended.